Introduction to Environmental Toxicology: Impacts of Chemicals Upon Ecological Systems - Landis, Wayne G. (CRC Press, 2009)
We have prepared this text because we had no suitable text for teaching courses introducing environmental toxicology and biochemistry. Portions of this book have already been used to teach an introduction to environmental toxicology and biochemical toxicology courses at Western Washington University and changes suggested by these students have been incorporated. In general these students have backgrounds in organic chemistry, ecology, calculus, and often biochemistry. We appreciate any feedback and these suggestions will be incorporated into, hopefully, further editions. One of the major difficulties in preparing this book has been the rate of change seen in the field. The U.S. Environmental Protection Agency prepared a new Framework for Ecological Risk Assessment, nonlinear dynamics has become a major part of ecological theory, and new methods of examining effects at the level of community and ecosystem have been developed during the writing of this book. Now it is two years later and we have made major revisions to this edition in order to keep pace with the field of environmental toxicology. Ecological risk assessment has become the operating paradigm and estrogen disruption has taken on a new importance. The field is more sophisticated in the data analysis tools that it uses and multivariate approaches are becoming more common in the literature. Perhaps the most recent development is the awareness that effects and risks must be seen on a regional scale. Multiple natural and anthropogenic stressors occur to a variety of connected habitats. In order to understand the patterns in the environment that result from the introduction of chemicals, we must take a large scale approach. It will be interesting to see what the next several years bring.